Increase of complex I and reduction of complex II mitochondrial activity are possible adaptive effects provoked by fluoride exposure - Pereira, Heloisa Aparecida Barbosa Silva; Araújo, Tamara Teodoro; Dionizio, Aline; Trevizol, Juliana Sanches; Pereira, Fabrício Soares; Iano, Flávia Godoy; Faria Ximenes, Valdecir [UNESP]; Buzalaf, Marília Afonso Rabelo (Elsevier, 2021)
Fluoride (F) can induce changes in the expression of several liver proteins, most of them localized in the mitochondria and its effect is dose- and time-dependent. This study analyzed the effect of distinct F concentrations and exposure periods on the mitochondrial activity of complex I-III and II-III in the liver. Thirty-six 21-day-old male Wistar rats were divided into 2 groups (n = 18) according to the duration of the treatment (20 or 60 days). They were subdivided into 3 subgroups (n = 6) according to the concentration of F (0 mg/L, 15 mg/L or 50 mg/L). After the experimental periods, the animals were anesthetized, liver mitochondria were isolated and stored for activity analyses. The determination of complexes II-III and I-III was based on the reduction of cytochrome c3+ to cytochrome c2+ performed spectrophotometrically. Bioinformatics analyses were performed using data from a previous study (Pereira et al., 2018). The mitochondrial complex I-III was significantly activated in the groups treated with 50 mgF/L for 20 days and 15 mgF/L for 60 days. The complex II-III was significantly reduced in the group treated with the higher F dose for 60 days. The networks indicated more changes in mitochondrial proteins in the group treated with the higher dose for 20 days; the reduction is probably linked to the activation of the complex I-III. The reduction in the complex II-III upon exposure to the higher F dose in the long term might be part of an adaptative mechanism of the body to counteract the deleterious effects of this ion on the energy metabolism. Liver, Fluoride, Oxidative stress, Mitochondria, Mitochondrial activity, Chronic exposure
Keywords: Chronic exposure; Fluoride; Liver; Mitochondria; Mitochondrial activity; Oxidative stress